Hydrothermal syntheses, luminescent properties, and temperature sensing of monodisperse Tb-doped NaCeF4 nanocrystals. Issue 2 (17th December 2020) - Qin, Haoran; Gong, Xinghong; Luo, Zundu; Huang, Yidong
Abstract : Monodisperse Tb-doped NaCeF4 nanocrystals were synthesized via a hydrothermal method. Abstract : Monodisperse Tb-doped NaCeF4 nanocrystals were synthesized via a hydrothermal method. The morphology, and room temperature and temperature dependent luminescent properties were investigated. Excited at 254 nm, the emissions of Ce 3+ at 270–370 nm and those of Tb 3+ at 475–700 nm can be observed. The strongest visible emission was observed in NaCeF4 :20 at% Tb with a quantum yield of 49%. The efficiency of energy transfer from Ce 3+ to Tb 3+ increases with the Tb 3+ doping concentration and reaches 95% for NaCeF4 :30 at% Tb. The ratio of Tb 3+ emission to Ce 3+ emission is sensitive to temperature, and the relative sensitivity was calculated to be 1.0% °C −1 at 60 °C. The mechanisms for this thermal dependence were analyzed in terms of non-radiative relaxation and energy migration.